Drawing the case studies together: synthesis of case studies and group discussions. Issue 1 (4th February 2019) - Gibson, Terry David; Tongwa, Aka Festus; Bari, Sarwar; Chantry, Guillaume; Gupta, Manu; Molina, Jesusa Grace; Shresha, Nisha; Norton, John; Parajuli, Bhubaneswari; Rahmawati, Hepi; Aretaake, Ruiti
Abstract : Purpose: The purpose of this paper is to individually examine the findings from eight case studies presented in this special issue and comparatively identify the findings regarding local learning and action. Design/methodology/approach: Underlying research questions regarding power and powerlessness in regard to addressing underlying risk factors affecting local populations form the basis for the discussion. Proceedings of a collaborative workshop conducted with the contributing authors are analysed qualitatively to identify learning relating to the research questions emerging from the case studies individually and collectively. Findings: A number of strategies and tactics for addressing underlying risk factors affecting local populations were identified from the case studies, including collaboration and cohesion. Campaigning, lobbying, communications and social mobilisation in an attempt to bridge the gap between local concerns and the decision-making of government and other powerful actors. Innovation and local mobilisation to address shortcomings in government support for disaster reduction and development. Communications as a first base to influence behaviour of both communities and government. Social change through empowerment of women to act in disaster reduction and development. Research limitations/implications: The outcomes of the action research conducted by the authors individually and collectively highlight the necessity for bridging different scales of action through a range of strategies and tactics to move beyond local self-reliance to influence on underlying risk factors. The action research process employed may have wider applications in gathering and formalising local-level experience and knowledge. Practical implications: The case studies and their analysis present a range of practical strategies and tactics to strengthen local resilience and address underlying risk factors which are replicable in other contexts. Originality/value: Practitioners are activists and do not often engage in critical reflection and analysis. The method presented here offers a means of achieving this in order to generate learning from local-level experience. The findings contribute to the consideration of cross-scale action to address underlying risk factors which impact local communities.